2018
DOI: 10.1177/1941738118800446
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sports Specialization in Elite Ice Hockey Players

Abstract: Background: Pediatric sports specialization, defined as intense year-round training in a single sport as a result of excluding other sports for more than 8 months per year, is common in the United States. There are demonstrated physical and social risks to early pediatric sports specialization (defined as before age 12 years). While thought to be needed to acquire appropriate experience and excel in a given sport, there remains little information on when athletes at the highest levels of their spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 10 publications
2
34
0
1
Order By: Relevance
“…All identified studies were cross-sectional (level III) or retrospective epidemiological (level IV); no prospective studies were identified. Fifteen of the 22 studies addressed career performance outcomes,22–36 whereas the remaining 7 looked at the effect of sport specialisation on specific task performances 20 21 37–41. Studies ranged from single-sport investigations in basketball, soccer, volleyball, field hockey, golf, track and field and ice hockey to those involving numerous sports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All identified studies were cross-sectional (level III) or retrospective epidemiological (level IV); no prospective studies were identified. Fifteen of the 22 studies addressed career performance outcomes,22–36 whereas the remaining 7 looked at the effect of sport specialisation on specific task performances 20 21 37–41. Studies ranged from single-sport investigations in basketball, soccer, volleyball, field hockey, golf, track and field and ice hockey to those involving numerous sports.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies defined specialisation as participating in a single sport, while one required the athletes to have quit other sports to focus on one sport 25. Two studies required specialisation to have occurred by a specific age of 12 or 14 years 23 38. Three studies used the Jayanthi 3-point scale to define sport specialisation level as low, moderate or high 20–22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cohort studies [5][6][7]15,16,18,19 of the relationship between early single-sport specialization and long-term sport performance have been conducted in non-US athletes. More recently, a growing number of studies of US athletes [20][21][22][23] have generated questions about the role of early single-sport specialization. However, few authors have explored the potential role of genetic influences on exceptional US athletes and compared such findings to a peer group whose participation did not advance beyond the youth level.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high school athletes who reported participating in a single sport for greater than 8 months of the year were more likely to give a history of hip injuries, but this study did not include ice hockey athletes. 15 In a small sample of NCAA Division I and III men's ice hockey athletes, approximately 46% (22/ 48) stated that they had specialized in ice hockey by the age of 14 years, 16 suggesting that a large proportion of ice hockey athletes may already be specialized by the time they reach high school.…”
mentioning
confidence: 99%